Radiation absorption and chemical reaction effects on rivlin-ericksen flow past a vertical moving porous plate - Sravanthi, C.S.; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
An analysis has been carried out to study the combined effects of radiation absorption and chemical reaction on an incompressible, electrically conducting and radiating flow of a Rivlin-Ericksen fluid along a semi-infinite vertical permeable moving plate in the presence of a transverse applied magnetic field. It is assumed that the suction velocity, the temperature and the concentration at the wall are exponentially varying with time.
Keywords: Rivlin-Ericksen fluid; radiation absorption; chemical reaction; variable temperature; concentration; suction